THE ROLE OF BUSINESS COMMUNICATION IN BRIDGING DEVELOPMENT STRATEGIES AND SOCIAL NETWORKS FOR THE ‘BUNDA COLLECTION’ FASHION MSME - Ladyva Aurellia; Dani Kurniawan; Ahmad Muntaha (Departemen Ilmu Komunikasi Universitas Andalas, 2025)
The sustainability and growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia is highly dependent on adaptive business strategies and effective utilization of social networks. This study aims to analyze how business development strategies and the role of networking support the success of Bunda Collection, a fashion MSME in Klaten, in developing from a micro scale to national and international levels. This research uses a qualitative case study approach with data collection methods through interviews, observation, and document analysis to gain in-depth understanding. The results showed that Bunda Collection succeeded through the implementation of comprehensive strategies, including product innovation, marketing digitalization, and operational efficiency. Networking proved to be an important factor in every phase of development, from gaining initial market access, expanding the reseller network, to surviving the crisis and pandemic. The synergy between a well-planned strategy and a strong network, which is also supported by organizations such as IWAPI, results in competitiveness, market expansion, and solid business resilience. This study confirms that the integration of the two is key to the success of MSMEs..